THE FREE NUTRITIOUS MEAL PROGRAM: A SOLUTION OR A BURDEN TO NATIONAL DEVELOPMENT? - Natasyah Luckmeida; Dhea Ananda; Shafira Zakkyatunnisa; Boni Saputra (Yayasan Amanah Nur Aman, 2026)
The Free Nutritious Meal Program (MBG) is a government policy aimed at improving the quality of human resources through fulfilling the nutritional needs of the community. This study aims to analyze the MBG program as both a solution and a burden in national development. The method used is a literature review by examining various journals, government data, and scientific sources related to nutrition, human development, and public policy. The results of the study indicate that the MBG program has the potential to improve nutritional quality, support the physical and cognitive development of children, and help reduce stunting and malnutrition rates. On the other hand, the implementation of the program faces several challenges, including large budget requirements, distribution constraints, uneven food quality, and the risk of budget misuse. In addition, the effectiveness of the program still depends on the quality of governance, supervision, and policy sustainability. Therefore, the MBG program needs to be implemented in a targeted, transparent, and sustainable manner in order to make an optimal contribution to national development.